Healthy Lifestyle As a Self-Presentation Strategy on Instagram (Qualitative Study on Z Generation in Medan City) - Nurbani; Sabilla Tri Ananda (Talenta Publisher, 2026)
This study aims to explain how the Z generation in Medan City implement Erving Goffman’s self-presentation strategy by using healthy lifestyle activity. This research uses qualitative method with observation and interview as data collection techniques and purposive sampling as an informant selection technique. Based on data from seven informants, it can be concluded that nformants demonstrate examplification and competence self-presentation strategy by updating their Strava application activity on social media Instagram and showing off several exercise activities with their sports community. In addition, presenting a healthy lifestyle on Instagram becomes more important motivation to informants than the benefit of healthy lifestyle itself.